Effect of Current and Pulse-on Time on Material Removal Rate and Surface Roughness of Tungsten Carbide in Electric Discharge Machine Die-sinking - Riyanto, Mochammad Deny; Andoko, Andoko; Suryanto, Heru (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
The focus of manufacturing for tungsten carbide applications often demands a smooth surface quality as the result of the Electric Discharge Machine (EDM) die-sinking process, especially in the manufacture of die and mold with tungsten carbide material processed using a die-sinking EDM machine. The purpose of this study is to analyze the effect of electric current and pulse-on time on the Material Removal Rate (MRR) and surface roughness of tungsten carbide. Through the experimental method, the parameters varied, namely electric current 17 A, 20 A, 23 A, and pulse-on time 30 µs, 55 µs, and 80 µs. MRR was calculated through weight loss. Surface roughness was obtained from a surface roughness tester and a Scanning Electron Microscope for surface morphology. The results showed that the highest material removal rate was 1.509 mm3/min at 23 A and 30 µs, and the lowest material removal rate was 0.262 mm3/min at 17 A and 80 µs. The highest surface roughness value was 4.278 µm at 23 A and 80 µs. The lowest surface roughness value was 2.166 µm at 17 A and 30 µs. The tungsten carbide surface topography results are crater, globule, crack, and porous. The greater the current used, the higher the MRR value and surface roughness. Meanwhile, the greater the pulse-on time used, the MRR value decreases, and the surface roughness increases.